The Causality Relationships between Economic Confidence and Fundamental Macroeconomic Indicators: Empirical Evidence from Selected European Union Countries - Demirel, Selim Koray; Artan, Seyfettin (International Journal of Economics and Financial Issues, 2017)
Economic confidence is an important tool in predicting macroeconomic changes. In this study, causality relationships between the confidence level and the fundamental macroeconomic indicators are analyzed using panel data analysis for 13 European Union countries for the period 2000: 1-2014: 12. According to the obtained results, a bidirectional causality relationship between the level of confidence and consumption expenditures, industrial production and inflation; a unidirectional relationship from the level of confidence to the unemployment rate; and a unidirectional relationship from interest rates to the level of confidence were detected. These results are compatible with the view that economic confidence is a leading indicator in explaining the changes in macroeconomic indicators. Keywords: Economic Confidence, Panel Causality Analysis, European Union, Macroeconomic Variables JEL Classifications: C33, E20, O52